Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd000980.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C for preventing and treating the common cold

Abstract: Background The role of oral vitamin C (ascorbic acid) in the prevention and treatment of the common cold has been a subject of controversy for at least sixty years. Public interest in the topic continues to be high and vitamin C continues to be widely sold and used as a preventive and therapeutic agent for this common ailment. Objectives To discover whether oral vitamin C in doses of 200 mg or more daily, reduces the incidence, duration or severity of the common cold when used either as continuous prophylaxis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
162
0
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(179 citation statements)
references
References 50 publications
3
162
0
14
Order By: Relevance
“…Further, plasma and leukocyte vitamin C concentrations fall rapidly with the onset of the infection and return to normal with the amelioration of the symptoms suggesting dosage with vitamin C could be beneficial for the recovery process [54] . A review of the large numbers of studies on a potential effect of vitamin C on the common cold and respiratory infections concluded that administration of 1 1 g/day had no consistent effect on the incidence of common colds, but supported a moderate benefit on duration and severity of symptoms which may also be of economic advantage [55] .…”
Section: Vitamin B 12mentioning
confidence: 99%
“…Further, plasma and leukocyte vitamin C concentrations fall rapidly with the onset of the infection and return to normal with the amelioration of the symptoms suggesting dosage with vitamin C could be beneficial for the recovery process [54] . A review of the large numbers of studies on a potential effect of vitamin C on the common cold and respiratory infections concluded that administration of 1 1 g/day had no consistent effect on the incidence of common colds, but supported a moderate benefit on duration and severity of symptoms which may also be of economic advantage [55] .…”
Section: Vitamin B 12mentioning
confidence: 99%
“…45 Previous studies were not able to show any benefit regarding the consumption of vitamin C and cancer prevention, urinary stone production 47 and reduction of common cold incidence. [48][49][50] Lee et al assessed the association between intake of vitamin C and mortality from cardiovascular disease in 1923 diabetic postmenopausal women. They concluded that intake of vitamin C from food had no association with mortality outcomes.…”
Section: Vitamin Cmentioning
confidence: 99%
“…In einer neueren Cochrane-Analyse von 2004 [83] zeigte sich, dass die prophylaktische, hochdosierte Gabe von Vitamin C die Inzidenz von grippalen Infekten in der (gesunden) Gesamtbevölkerung nicht reduzieren kann.…”
Section: Leukotrienantagonisten Die Gabe Desunclassified